Religious symbols and state regulation - McGoldrick, Dominic (Brill, 2017)
Religious symbols are historically significant and socially powerful. They have many forms and functions. Their legal regulation presents difficult challenges for courts, particularly international courts. This article examines how the European Court of Human Rights has approached the regulation of the regulation of religious symbols by national jurisdictions. It submits that the fundamental touchstone of the Court’s jurisprudence lies in its approach to secularism. It has accepted secularism as consistent with the values underpinning the Convention. This is a strategic and sensible approach. There are limits imposed by the prohibitions on discrimination and indoctrination. Beyond secularism there have been tentative steps towards a balancing / reasonable accommodation approach but the Court appreciates that the balances are difficult ones on which reasonable people, and even reasonable states, may legitimately disagree.